2022
DOI: 10.3390/toxics10020056
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Mitochondrial Metabolites in Persistently Symptomatic Individuals after a GBCA-Assisted MRI

Abstract: Despite the impressive safety of gadolinium (Gd)-based contrast agents (GBCAs), a small number of patients report the onset of new, severe, ongoing symptoms after even a single exposure—a syndrome termed Gadolinium Deposition Disease (GDD). Mitochondrial dysfunction and oxidative stress have been repeatedly implicated by animal and in vitro studies as mechanisms of Gd/GBCA-related toxicity, and as pathogenic in other diseases with similarities in presentation. Here, we aimed to molecularly characterize and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…28 Most interesting, a recent study used untargeted mass spectroscopybased metabolomic analyses to investigate the plasma metabolite alterations after Gd administration. 20 Compared with healthy controls, patients with Gd-deposition disease showed differences in 45 biochemicals, mostly related to mitochondrial function, similar to our findings in the brain. 20 We propose that the observed increased levels of Cr in case participants might indicate a disturbance in cellular energy homeostasis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…28 Most interesting, a recent study used untargeted mass spectroscopybased metabolomic analyses to investigate the plasma metabolite alterations after Gd administration. 20 Compared with healthy controls, patients with Gd-deposition disease showed differences in 45 biochemicals, mostly related to mitochondrial function, similar to our findings in the brain. 20 We propose that the observed increased levels of Cr in case participants might indicate a disturbance in cellular energy homeostasis.…”
Section: Discussionsupporting
confidence: 88%
“…Preclinical and clinical studies have reported in vitro neurotoxic effects of Gd exposure due to impairment of mitochondrial function and mitochondrial metabolic alterations subsequent to gadolinium deposition. 19,20 We hypothesize that Cr and lactate will show alterations due to disturbed mitochondrial metabolism. We also hoped this study would contribute to the understanding of the molecular and cellular ramifications of Gd deposition.…”
mentioning
confidence: 99%
“…Based on these works on cytokines, our present theory is that GDD is primarily an immune-mediated inflammatory disease (IMID) that has a principal effect on tissue-resident memory T cells (NT), which have been described as the principal mediating cell in Crohn disease 18,19 and asthma 17 . Other researchers have looked at other cell products elevated in GBCA exposure and GDD, and have shown elevated serum biomarkers for mitochondrial damage 5,20,21 …”
Section: Diagnosismentioning
confidence: 99%
“…In recent years, GDD has achieved generalizability, which is a critical requirement for disease recognition. Three independent groups have reported in the peer-reviewed literature on GDD 1–5 . In this review, we will describe observations reflecting whether they have achieved broad acceptance as a theory (BAT) or if it is a novel theory/opinion of our team (NT).…”
mentioning
confidence: 99%
See 1 more Smart Citation